Review of Lucia Dell’Aia (editor), Elsa Morante. Myth and literature (Ledizioni, 2021) (ENTHYMEMA, 2022)
Review of Lucia Dell’Aia (editor), Elsa Morante. Myth and literature (Ledizioni, 2021).
Keywords: Elsa Morante; Myth; Intertextuality; Contemporary Literature; Comparative Literature